Age-Associated Structural Changes in Synovial Membranes of Rabbits and Dogs: A Comparative Review - Sagiroglu, Ayse Oya (Medwell Online, 2012)
Synovial membrane has considerable importance in the physical activities of all the mammalian. As a consequence, different aspects of synovial membrane have been studied in detail by numerous scientists. As age related changes and deformations are essential in understanding and curing of rheumatic and other illnesses associated with aging, these subjects have the prime importance. General appearance of the synovial membrane changes from small, shiny, smooth and light colored in young dogs and rabbits to large, rough and grayish colored in the olds. The dog's intima get thicker and more layered with aging and in rabbits intima cell types changes only. In rabbits and dogs connective tissue types of subintima changes from areolar, adipose and areola-adipose types connective tissue types to fibrous type with age increase. The collagen fibers are rare and scattered in young animals and the fibers increase gradually and form bundles and bands in. middle age and old animals. The elastic fibers increase and thicken with aging in the synovial membrane of dogs. In rabbits trend of decrease occur from young towards old animals. In dog and rabbit synovial membranes capillaries are plenty in. young animals and decrease with increasing age. In other members of the synovium age, associated changes are not particularly clear.
Keywords: Synovial membrane; dogs; rabbits; age related changes; intima; subintima